MARCO ANTONIO SANTAMARÍA (ed.), The Derveni Papyrus: Unearthing Ancient Mysteries. Papyrologica Lugduno-Batava, 36, Leiden; Boston: Brill 2019, pp. viii+ 173, €116,00, ISBN 978-90-04-38484-2. - Janko, Richard (Exemplaria Classica, 2020)
Reseña